The Key Success Factors: A Case Study of UNIQLO - Mohamad Mirza; Ashutosh Verma; Daisy Mui Hung Kee; Awatif Awatif; Farah Nur Qistina; Muhammad Khairul Aswadi (Journal of the Community Development in Asia (JCDA), 2020)
This paper aims to investigate how the UNIQLO, the global Japanese fast fashion retailing group, drives their organization towards success. UNIQLO has a good product quality by introducing Heat Tech range of cold weather underwear lines which targeted at warm weather with affordable price. Besides, UNIQLO continues to develop its product via research and development to meet the needs of their customers. UNIQLO stores particularly are distinctive and have a clear positioning in the market. In 2014, UNIQLO launched its mobile online store through the smartphone app. UNIQLO emphasizes on giving the best satisfaction to their customers. The paper presents the factors that lead to organizational success in UNIQLO. These findings will have considerable implications for academics as well as practitioners. Finally, the paper also provides direction for future research.